2017
DOI: 10.1007/s11270-017-3286-8
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Levels of Atmospheric Ammonia in a Mediterranean Holm-Oak Forest in North-Eastern Spain

Abstract: Despite recent regulations, atmospheric ammonia (NH3) emissions have not changed much over the last decades and excessive nitrogen remains as one of the major drivers for biodiversity changes. To prevent deleterious effects on species and ecosystems it is very important to establish safety thresholds, such as those defined by the Critical Level (CLE) concept, "the concentration above which direct adverse effects on receptors may occur, based on present knowledge". Empirical critical levels of atmospheric NH3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition to the loss of habitat, agricultural activities, mainly intensive farming with fertilizers and intensive animal husbandry, have a great impact on the atmosphere (Fao, 2006). These activities are the main anthropogenic sources of atmospheric nitrogen compounds (Galloway et al, 2003) and their effects on terrestrial vegetation and lichens has been widely reported (Aguillaume et al, 2017;Boltersdorf and Werner, 2014;Frati et al, 2008Frati et al, , 2007Krupa, 2003;Paoli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the loss of habitat, agricultural activities, mainly intensive farming with fertilizers and intensive animal husbandry, have a great impact on the atmosphere (Fao, 2006). These activities are the main anthropogenic sources of atmospheric nitrogen compounds (Galloway et al, 2003) and their effects on terrestrial vegetation and lichens has been widely reported (Aguillaume et al, 2017;Boltersdorf and Werner, 2014;Frati et al, 2008Frati et al, , 2007Krupa, 2003;Paoli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kappelle & Sipman 1992;Upreti & Chatterjee 2000;Oran & Oztürk 2012;Villella et al 2013b;Pérez-Pérez et al 2015;Marmor et al 2017;EI Mokni et al 2018). Oak-dominated habitats are often subject to intense anthropogenic influences that have substantial effects on lichen communities, such as burning, urbanization, and conversion to agriculture (van Herk 2001;Insarov et al 2010;Aguillaume et al 2017;Güvenç & Öztürk 2017). In the Pacific Northwest humans have recently repressed wildfires in oak-dominated habitats leading to invasion by other tree species, such as conifers (Sugihara and Reed 1987;Engber et al 2011).…”
Section: Introductionmentioning
confidence: 99%